A comprehensive nonlocal surface-piezoelectricity model for thermal and vibration analyses of piezoelectric nanoplates. (1st May 2021) - Khorshidi, Korosh; Bahrami, Mahdi; Eshaghi, Mehdi; Ghasemi, Mohsen
Highlights: Surface effects on vibration behavior of piezoelectric nanoplates are discussed. The electro-thermal vibration of nanoplate is investigated. The Gurtin and Murdoch theory is applied to capture surface effects in nanoplate. The nonlocal elasticity theory is used to capture the nano-scale effects. The results show significant effects of surface parameters on vibration behavior. Abstract: The present study employs the modified shear deformation plate theories to investigate the effects of surface parameters on the electro-thermal vibration characteristics of the piezoelectric nanoplates. The nonlocal surface piezoelectricity theory based on Gurtin-Murdoch surface elasticity and Eringen's nonlocal theory are incorporated to take the small-scale effects into account. The governing equations of motion of the structure are derived and solved using the Hamilton's principle and Galerkin method. Validity of the proposed model is demonstrated by comparing the results with those available in the literature. The verified model is employed to investigate the effects of different parameters such as surface residual stress, surface elastic constants, surface piezoelectricity, nonlocal parameter, aspect ratio, thickness ratio, temperature, and applied voltage on the dynamic characteristics of the structure. The results report significant contribution of the surface parameters in vibration characteristics of the piezoelectric nanoplates.